Pemetaan Zona Potensi Penangkapan Ikan Pelagis Berbasis Data Satelit Multi Parameter di Wilayah Pengelolaan Perikanan 714 - Marpaung, Sartono; Supriatna, Supriatna; Manessa, Masita Dwi Mandini; Yati, Emi (Bumi Lestari; Vol 25 No 2 (2025), 2025)
Fisheries management area (FMA) 714 has an abundance of pelagic resources. To optimize this potency, it is important to map the potential pelagic fishing zone (PPFZ) using multi-parameter satellite data. The methods used to process the sea surface temperature and sea surface height data are single image edge detection and intersect. Based on the analysis of monthly and seasonal PPFZ information, there was a significant increase in the amount of PPFZ points during the first and second transition periods. The increase in the first transition period occurred in March-April, and in the second transition period, the increase occurred in September-October. The increase in the amount of PPFZ points is 17%. The maximum amount of PPFZ points occurred in October with 5.367 points. The decreasing of PPFZ points occurred in the wet and dry seasons. The decrease in the wet season occurred from December to February. The decrease in the dry season occurred in June-July. The decrease of PPFZ points is 15%. The minimum number of PPFZ points was in February, with 3.045 points. Changes in the climate seasons have a strong influence on the changes in the distribution pattern and amount of PPFZ points. The distribution map of the PPFZ points with high and very high density predominantly occurred in the southern part of FMA 714. PPFZ with low and medium density occurred in the center of the area studied.   Keywords: fishing zone; mapping; pelagic ; sea surface height; s ea surface temperature